Genetics implicate common mechanisms in autism and schizophrenia: synaptic activity and immunity. Issue 8 (17th March 2017) - Liu, Xiaoming; Li, Zhengwei; Fan, Conghai; Zhang, Dongli; Chen, Jiao
Abstract : The diagnosis of debilitating psychiatric disorders like autism spectrum disorder (ASD) and schizophrenia (SCHZ) is on the rise. These are severe conditions that lead to social isolation and require lifelong professional care. Improved diagnosis of ASD and SCHZ provides early access to medication and therapy, but the reality is that the mechanisms and the cellular pathology underlying these conditions are mostly unknown at this time. Although both ASD and SCHZ have strong inherited components, genetic risk seems to be distributed in hundreds of variants, each conferring low risk. The poor understanding of the genetics of ASD and SCHZ is a significant hurdle to developing effective treatments for these costly conditions. The recent implementation of next-generation sequencing technologies and the creation of large consortia have started to reveal the genetic bases of ASD and SCHZ. Alterations in gene expression regulation, synaptic architecture and activity and immunity seem to be the main cellular mechanisms contributing to both ASD and SCHZ, a surprising overlap given the distinct phenotypes and onset of these conditions. These diverse pathways seem to converge in aberrant synaptic plasticity and remodelling, which leads to altered connectivity between relevant brain regions. Continuous efforts to understand the genetic basis of ASD and SCHZ will soon lead to significant progress in the mechanistic understanding of these prominent psychiatric disorders and enable the development of disease-modifying therapies for these devastating conditions.